Magnetic resonance of rubidium atoms passing through a multi-layered transmission magnetic grating. (26th April 2017) - Nagata, Y; Kurokawa, S; Hatakeyama, A
Abstract: We measured the magnetic resonance of rubidium atoms passing through periodic magnetic fields generated by two types of multi-layered transmission magnetic grating. One of the gratings reported here was assembled by stacking four layers of magnetic films so that the direction of magnetization alternated at each level. The other grating was assembled so that the magnetization at each level was aligned. For both types of grating, the experimental results were in good agreement with our calculations. We studied the feasibility of extending the frequency band of the grating and narrowing its resonance linewidth by performing calculations. For magnetic resonance precision spectroscopy, we conclude that the multi-layered transmission magnetic grating can generate periodic fields with narrower linewidths at higher frequencies when a larger number of layers are assembled at a shorter period length. Moreover, the frequency band of this type of grating can potentially achieve frequencies of up to hundreds of PHz.